2022
DOI: 10.3847/1538-4357/aca2a5
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Spectral Lines for Measuring Chromospheric Magnetic Fields

Abstract: This paper identifies spectral lines from X-ray to IR wavelengths which are optimally suited to measuring vector magnetic fields as high as possible in the solar atmosphere. Instrumental and Earth's atmospheric properties, as well as solar abundances, atmospheric properties, and elementary atomic physics are considered without bias toward particular wavelengths or diagnostic techniques. While narrowly focused investigations of individual lines have been reported in detail, no assessment of the comparative meri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…It be interesting to explore the kinds of observations presented here with other data sets, especially in regions of quiet Sun where, although the He I lines are weak, they can still be used to probe conditions at the coronal base (Harvey & Hall 1971;Rüedi et al 1996;Lagg et al 2004). In the case that the He I lines are too weak to explore at sufficiently high angular resolution, one might use the 854.2 nm line of Ca II, or if selected for flight, various lines of Mg II and Fe II in the UV region (259-281 nm) using the Chromospheric Magnetism Explorer instrument (Gilbert & CMEx Team 2023; see Judge et al 2021Judge et al , 2022 for reasons to observe in this region).…”
Section: Discussionmentioning
confidence: 99%
“…It be interesting to explore the kinds of observations presented here with other data sets, especially in regions of quiet Sun where, although the He I lines are weak, they can still be used to probe conditions at the coronal base (Harvey & Hall 1971;Rüedi et al 1996;Lagg et al 2004). In the case that the He I lines are too weak to explore at sufficiently high angular resolution, one might use the 854.2 nm line of Ca II, or if selected for flight, various lines of Mg II and Fe II in the UV region (259-281 nm) using the Chromospheric Magnetism Explorer instrument (Gilbert & CMEx Team 2023; see Judge et al 2021Judge et al , 2022 for reasons to observe in this region).…”
Section: Discussionmentioning
confidence: 99%
“…Emission lines from various chlorine-like ions have been observed in a number of astrophysical sources, such as the solar corona [58], stellar chromospheres [59], or the interstellar medium [60]. The intensity ratios of these lines are typically temperatureand density-sensitive, and they can thus be utilized for the diagnostics of astrophysical plasma.…”
Section: Collision Strengths For Chlorine-like Ionsmentioning
confidence: 99%
“…Among these lines, two Fe II spectral lines stand out: a relatively weak emission line at 279.79 nm and an absorption line at 280.66 nm, just at the red edge of the CLASP2 spectral window. Recent investigations have suggested that the Fe II lines located blueward of the CLASP2 spectral region are of complementary interest for diagnosing the magnetism of the solar chromosphere (see Judge et al 2021Judge et al , 2022. A quantitative study of the polarization signals and magnetic sensitivity of the Fe II spectral lines in the near-UV region of the solar spectrum has been recently published by Afonso Delgado et al (2023a), but the Fe II lines located in the CLASP2 spectral region were not included in their work.…”
Section: Introductionmentioning
confidence: 99%